Magnetoelectronic memories last and last. - Johnson, M.
Nonvolatile RAMs built with thin films of ferromagnetic material are poised to challenge dynamic and nonvolatile memories based on conventional semiconductors. At the root of the excitement are electronic devices with a ferromagnetic component that lets them not only switch between two stable states in one clock cycle but also retain the state they are in when power is removed. The compact design and simple operation of magnetoelectronic devices make them ideal storage cells for fast random-access memory (RAM). Prototypes improve by several orders of magnitude on the speed, power, and reliability of semiconducting floating-gate nonvolatile memory and have achieved cell sizes and operating speeds that are competitive with dynamic (volatile) RAM. Further off in the future is the intriguing prospect of instantaneously reprogrammable logic. Magnetoelectronic devices may be grouped according to the physics of their operation into three main categories: hybrid ferromagnet semiconductor structures, magnetic tunnel junctions, and all-metal spin transistors and spin valves
Keywords: All-metal spin transistors; All-metal spin valves; Electronic devices; Fast random-access memory; Ferromagnetic thin films; Hybrid ferromagnet semiconductor structures; Magnetic tunnel junctions; Magnetoelectronic devices; Magnetoelectronic memories; Nonvolatile RAM; Stable states switching; Storage cells